(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The main conclusion of this work of the “Ordenanzas Reales de Castilla”, or what is the same “Ordenamiento de Montalvo”, is make clear that most of laws that contains the first recompilation of Castilla laws, dated of 1484, during the reign of Reyes Católicos, were aplicated during almost 400 years, because they were also included in the “Nueva Recopilación” of 1567, during the reign Felipe II, as well as the “Novísima Recopilación” of 1805 that was promulgated by Carlos IV.